AYURVEDIC MANAGEMENT OF MALE INFERTILITY DUE TO OLIGOSPERMIA AND VARICOCELE: A CASE STUDY (International Journal of Ayurveda and Pharma Research, 2021)
Infertility is defined as the failure of a couple to achieve conception after one year of regular sexual intercourse without any contraception. Male infertility can be defined as any health issue in a man that lowers his chance of impregnating a fertile female partner. Current data reveals that about one third of all infertility cases is due to male factor defect. Oligospermia is a condition of suboptimal concentration of spermatozoa in the ejaculated semen to cause successful fertilization of an ovum. Hence the management of this issue is of utmost importance in the current days. Ayurveda addresses the male factor defects under broad classification of Ashtavidhasukradushti in which oligospermia can be correlated to Ksheenasukra. A 33yr old male with 3 years of married life diagnosed with oligospermia, increased viscosity of semen and bilateral grade I varicocele and wife aged 26yrs with regular, ovulatory cycles and with apparently no reproductive issues, were treated according to Ayurvedic principles. After Deepana pachana with Pippalyasavam and Vicharana snehapana with Sukumara ghritha and Mahakalyanaka ghritha, repeated Virechana with Avipathi choornam was given. Kokilaksha Kashayam and Varanadi Kashayam was given internally. Bala thailam and Pinda thailam was advised for external application. Follow up showed improvement in Seminal parameters in terms of sperm concentration, viscosity and resulted in pregnancy. The present case signifies the importance of Ayurvedic treatment in bringing a positive outcome in the field of male infertility.